PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK MATERI KEBERAGAMAN AGAMA BERBASIS EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SDN BURENGAN 1 - Rizka wahyu Noerlaily; Karimatus Saidah; Wahid Ibnu Zaman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of students on the material of religious diversity in Indonesia and the minimal use of innovative and interactive learning media. This condition has an impact on students' less than optimal understanding of the material. The purpose of this study is to develop Pop Up Book learning media based on the Example Non Example model to improve the learning outcomes of second-grade students at SDN Burengan 1, Kediri City. The development model used is ADDIE which includes the stages of analysis, design, development, implementation, and evaluation. Data collection instruments include media and material expert validation questionnaires, student and teacher practicality questionnaires, and learning outcome tests. Data analysis techniques are carried out to measure the validity, practicality, and effectiveness of the media. The results of the study show that (1) the validity of the media based on the assessment of media experts is 88% and material experts is 91%, so it is categorized as very valid; (2) the practicality of the media based on teacher responses is 97% and students is 98%, indicating that the media is very practical; and (3) the effectiveness of the media based on the results of the students' post-test in the limited test reached an average of 86, and the extensive trial reached an average of 90, which shows that the media is very effective. The Pop Up Book media based on Example Non Example is stated to be very valid, very practical, and very effective to be applied in learning the material on religious diversity.